Determination of Vanadium, Niobium and Tantalum by HPLC using 2-(2-Quinolinylazo)-Resorcin as Pre-column Derivatization Reagent - HE, RONG; CHEN, JUN; HUANG, ZHANGJIE; YIN, JIAYUANG; YANG, GUANGYU (Asian Journal of Chemistry, 2010)
A new method for analysis of vanadium, niobium and tantalum as metal chelates of 2-(2-quinolinylazo)-resorcin (QAR) was developed using high performance liquid chromatography. The vanadium, niobium and tantalum ions were pre-column derivatized with QAR to form coloured chelates. The V-QAR, Nb-QAR, Ta-QAR were enriched by solid phase extraction with C18 cartridge. The enrichment factor of 100 was achieved by eluted the retained chelates from the cartridge with tetrahydrofuran (THF). The chelates were separated on a ZORBAX Stable Bound, 4.6 × 50 mm, 1.8 μm rapid analytical column with acetonitrile-water (42:58, v/v) containing 0.01 mol L-1 pH 4.5 phosphatic buffer and 0.01 mol L-1 of citrate as mobile phase. The vanadium, niobium and tantalum chelates were separated completely within 2.5 min. The detection limits (S/N=3) of vanadium, niobium and tantalum are 3.2, 3.2 and 3.8 ng L-1, respectively. This method was applied to the determination of vanadium, niobium and tantalum in alloy steel, water and geologic samples with good results.